1999
DOI: 10.2134/jeq1999.00472425002800020023x
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Drainage Loss of Particles and Phosphorus from Field Plot Experiments and a Tile‐Drained Catchment

Abstract: Movement of particles by water through the soil can be a significant pathway for P transport to surface waters in certain soil types. Our objective was to describe and quantify particulate matter (PM), particulate phosphorus (PP) and dissolved phosphorus (DP) transport tile drains during controlled plot experiments. The results were compared to corresponding studies of natural storm events in the tile‐drained catchment as a whole. Six rain simulations (irrigation 15.3–37 mm) were carried out at two 25 m2 plots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
80
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 0 publications
10
80
1
Order By: Relevance
“…Such losses were of a similar magnitude than annual losses measured on similar soils by Petersen et al (2004) or Sogon et al (1999). At the event scale, particles were mainly transported to the drain at the early beginning of drainflow events, the maximum concentrations in particles being often observed before the peak drainwater discharge (Grant et al, 1996;Kronvang et al, 1997;Penven et al, 1998;Laubel et al, 1999;Petersen et al, 2004). Subsequently, both the drainflow and its particulate matter (PM) concentrations rapidly declined with time.…”
Section: Amounts and Dynamic Of Particle Losses At The Drainage Netwomentioning
confidence: 77%
See 4 more Smart Citations
“…Such losses were of a similar magnitude than annual losses measured on similar soils by Petersen et al (2004) or Sogon et al (1999). At the event scale, particles were mainly transported to the drain at the early beginning of drainflow events, the maximum concentrations in particles being often observed before the peak drainwater discharge (Grant et al, 1996;Kronvang et al, 1997;Penven et al, 1998;Laubel et al, 1999;Petersen et al, 2004). Subsequently, both the drainflow and its particulate matter (PM) concentrations rapidly declined with time.…”
Section: Amounts and Dynamic Of Particle Losses At The Drainage Netwomentioning
confidence: 77%
“…Laubel et al (1999) showed that loss rates were thus higher during the first autumn storm after the dry season than during winter storms. This seasonal trend was attributed to the gradual decrease of the easily available particle pool produced during the dry season due to both biological activity and soil drying (Grant et al, 1996;Kronvang et al, 1997;Laubel et al, 1999), but contradictory results are also reported (Petersen et al, 2004).…”
Section: Amounts and Dynamic Of Particle Losses At The Drainage Netwomentioning
confidence: 97%
See 3 more Smart Citations